Plasmablastic lymphoma presenting as sino-nasal mass in a child: a case report - Arjun Kachhwaha; Kavya Ronanki; Prisla Maria Dalton; Nikhil Nagpal; Uttam Kumar Nath (Pediatric Hematology Oncology Journal, 2025)
Background: Plasmablastic lymphoma (PBL) is a very aggressive non-Hodgkin lymphoma that mostly occurs in immunocompromised individuals, especially those affected with human immunodeficiency virus (HIV) infection, and is rarely reported in children. Case presentation: An 8-year-old female case of HIV on highly active antiretroviral therapy (HAART) for the last 2 years presented with epistaxis, and a left sino-nasal mass for the last 6 months and a rapidly progressing left orbital mass for one month. Endoscopic debulking surgery revealed the diagnosis of PBL. She was managed with CODOX-M (cyclophosphamide, vincristine, doxorubicin, high-dose methotrexate) alternating with IVAC (ifosfamide, etoposide, and high-dose cytarabine) for 2 cycles each. The patient achieved complete morphological remission, confirmed on positron emission tomography-computed tomography (PET/CT) and local radiation was then given. HAART was withheld temporarily during the CODOX-M cycle owing to significant drug interaction and liver toxicity but continued during IVAC. The patient has been in remission for the 13 months following completion of therapy. Conclusion: PBL is an aggressive disease that requires intensive chemotherapy. It is challenging to monitor adverse effects and drug-drug interaction while on chemotherapy and HAART together. Close monitoring and follow-up are needed, as over half of patients will relapse post-remission.